Anaerobic nonylphenol ethoxylate degradation coupled to nitrate reduction in a modified biodegradability batch test - Luppi, Lorena I. (2007)
The aim of this work was to elucidate the role of nitrate as a terminal electron acceptor on the biodegradation of NPEO. We have characterized the products of NPEO degradation by mixed microbial communities in anaerobic batch tests by means of HPLC, 1H NMR and GC-MS. Anaerobic degradation of NPEO was strictly dependent on the presence of nitrate. Within seven days of anoxic incubation, NP2EO appeared as the major degradation product. After 21 days, NP was the main species detected, and was not degraded further even after 35 days. Nitrate concentration decreased in parallel with NPEO de-ethoxylation. A transient accumulation of nitrite was observed within the time period in which NP formation reached its maximum production. The observed generation of nonylphenol coupled to nitrate reduction suggests that the microbial consortium possessed an alternate pathway for the degradation of NPEO, which was not accessible under aerobic conditions.